Self-Efficacy, Psychological Flexibility, and Basic Needs Satisfaction Make a Difference: Recently Graduated Psychologists at Increased or Decreased Risk for Future Health Issues - Schéle, Ingrid; Olby, Matilda; Wallin, Hanna; Holmquist, Sofie (Frontiers in Psychology, 2021)
The transition from university to working life appears a critical period impacting human service workers' long-term health. More research is needed on how psychological factors affect the risk. We aimed to investigate how subgroups, based on self-efficacy, psychological flexibility, and basic psychological need satisfaction ratings, differed on self-rated health, wellbeing, and intention to leave. A postal survey was sent to 1077 recently graduated psychologists in Sweden (≤3 yrs. from graduation), response rate 57.5%, final sample 532 (75 % women, 23 % men). A hierarchical cluster analysis resulted in a satisfactory eight-cluster solution. We identified two at-risk subgroups, displaying the lowest scores on health and wellbeing, and one potential low-risk subgroup with the highest ratings on said variables. The “Low risk?” group rated high on all three psychological constructs, a positive transition to working life, a work environment where resources balanced relatively high emotional demands, good health, and wellbeing. Almost the complete opposite ratings characterized the potential risk groups. “Quitting?” scored significantly higher than “Getting sick?” on self-efficacy and psychological flexibility as well as actively seeking new employment and reporting daily thoughts on leaving the profession. We suggest that a combination of low self-efficacy and psychological flexibility could increase the risk of individuals staying despite suboptimal working conditions. With combined higher self-efficacy and psychological flexibility, individuals in similar circumstances appear more inclined to quit. We conclude that the ways recently graduated psychologists rate their self-efficacy, psychological flexibility, and basic needs satisfaction appears to be reflected in their self-rated health and wellbeing.